Yonatan Adler. Between Yahwism and Judaism. Judean Cult and Culture during the Early Hellenistic Period (332-175 BCE). - Gienini, Olga (Antiguo Oriente, 2026)
Yonatan Adler seeks to define the nature of Judean cult and culture during the Early Hellenistic period. He considers this to be a transitional time between the preceding Persian era and the subsequent Late Hellenistic and Roman periods. Specifically, he attempts to determine whether there was cultural continuity with past Yahwism or whether something akin to nascent Judaism emerged during this period. The author’s first criterion is to focus on what he vaguely names “Judean society at large”, which he believes was primarily represented by the masses of ordinary people who made up the majority of the population, as opposed to “any small number of non-representative Judean literati” (65). This establishes the discretionary selection of material that he will include or reject in his study a priori. The book begins with an introduction, followed by five chapters. Each chapter describes the material it will cover: “Administrative Structures;” “Torah Law;” “Cultic Worship of YHWH;” “Adoption of Greek Cultural Elements;” and “Literary Reception.” It concludes with a brief conclusion. The book also includes maps, figures and graphics.